Cancer-related fatigue in childhood cancer survivors: A systematic scoping review on contributors of fatigue and how they are targeted by non-pharmacological interventions. (November 2022) - Levesque, Ariane; Caru, Maxime; Duval, Michel; Laverdière, Caroline; Marjerrison, Stacey; Sultan, Serge
Abstract: Objectives: We aimed to identify contributors to cancer-related fatigue (CRF), explore non-pharmacological interventions addressing CRF, and highlight which contributors were targeted by these interventions in childhood cancer survivors. Methods: We performed a search in various databases and used the PRISMA-ScR checklist. Findings were synthesized in various different tables and figures in accordance with our objectives. Results: We included 49 articles in this systematic scoping review. We identified 59 significant contributors. Depression and physical activity level were some of the most studied significant contributors. Ten interventional studies were identified (e.g., yoga, physical activity intervention) that addressed 6 contributors (e.g., physical activity level). Discussion: This review is the first to describe and relate contributors and non-pharmacological interventions targeting CRF in childhood cancer survivors. Important clinical implications could be derived from the variety of factors explaining CRF and how it is currently addressed. Graphical Abstract: ga1 Highlights: Identification of contributors, non-pharmacological interventions, and description of contributors targeted by interventions Common candidate and significant contributors to CRF: depression, physical activity level, anxiety, pain, and sleep quality. Interventions targeting contributors: exercise counseling, cognitive-behavior therapy, yoga, and physical activity